THE STRENGTH BEHIND GROWTH: EXPLORING METAPHORS IN PAUL LAURENCE DUNBAR’S POEM, THE SEEDLING - Fitriyah, Fitriyah; Suroso, Aisyah Ahzahra; Maharani, Arvina Septa (Universitas Islam Sumatera Utara (UISU), 2024)
This research analyzes the types of metaphors in Paul Laurence Dunbar’s ‘The Seedling’ using Lakoff and Johnson’s conceptual metaphor theory. A metaphor is a figure of speech that compares two different things. A metaphorical poem has the ability to create and translate the figurative language contained in the content of the poem, especially where there are deep personal and emotional experiences”.